(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
This study examined prevention of deviant behaviours as perceived by secondary school teachers in Ilorin metropolis, Kwara State. Three research hypotheses were raised to guide the study. The total population of the study was four hundred and eighty-three (483) Secondary school teachers. Descriptive survey research design was employed to collect the data. Simple random sampling technique was used to select the three hundred (300) respondents that participated in this study. The main instrument used was a questionnaire tagged “Prevention of deviant behaviours” (PDBQ). Both face and content validity of the instrument were established. The psychometric analysis was based on validity and reliability measure of the research instrument. The t-test and Analysis of Variance (ANOVA) statistical tools were used to test the three null hypotheses. The result of ANOVA showed a significant difference in the perception of secondary school teachers in Ilorin metropolis on the prevention of deviant behaviours and hence, Duncan Multiple Range Test (DMRT) was used as post-hoc test to determine the group(s) that contributed to the significant difference. The findings based on the respondent’s expression for the prevention of deviant behaviours was that the school management must be conversant with the rules and cooperation between religious leaders, parents and school teachers with a mean score of 3.13. The result of the test used on the first hypothesis confirmed that significant difference exists on the basis of religious affiliation. Based on the findings the researcher concluded that, the teachers, school management, home and society at large should work toward developing better citizens and counselling made an integral part of the training of students. Based on the findings, the following recommendations were made: Effective communication should be employed at all levels of education to identify and prevent deviant behaviours, reducing students socially unacceptable acts such as pick-pocketing, running away from home, gang involvement, precocious sexual activities and truancy.